Attractors of Compactly Generated Semigroups of Regular Polynomial Mappings. (11th November 2018) - Alghamdi, Azza; Klimek, Maciej; Kosek, Marta
Abstract : We investigate the metric space of pluriregular sets as well as the contractions on that space induced by infinite compact families of proper polynomial mappings of several complex variables. The topological semigroups generated by such families, with composition as the semigroup operation, lead to the constructions of a variety of Julia-type pluriregular sets. The generating families can also be viewed as infinite iterated function systems with compact attractors. We show that such attractors can be approximated both deterministically and probabilistically in a manner of the classic chaos game.